Comparing the Performance of LoRaWAN and MQTT Protocols for IoT Sensor Networks - Fauzan Prasetyo Eka Putra; Ubaidi; Holipah; Moch. Amir Mahmud; Reni Paradina (SEULANGA SYSTEM PUBLISHER, 2024)
IoT (Internet of Things) Sensor Networks are an important infrastructure in facilitating data collection from various widespread sensor devices. In this context, the selection of the right communication protocol plays a key role in determining the performance and efficiency of the network. Two commonly used protocols in IoT sensor networks are LoRaWAN and MQTT. The study aims to compare the performance between LoRaWAN and MQTT protocols for IoT sensor networks in various critical aspects such as differing in terms of the number of end devices, data transmission period, gateway radius distance, and power consumption, Data collected from sensors connected to LoRaWAN and MQTT gateways. The data includes Throughput, Packet Loss, and power consumption The results show that LoRaWAN is generally superior to MQTT in terms of Throughput and Packet Loss, especially at long gateway radius distances. LoRaWAN also has lower power consumption compared to MQTT, but MQTT also excels in Data Transmission Period and Number of End Devices in terms of Throughput and Packet Loss. The selection of the right protocol should be based on the needs and characteristics of the application to be implemented.